Gamma rays and EMS induced mutants in Indian mustard (Brassica juncea) - EMS,; AT Nartam,; MG Badukale,; NA Mohurle, (Journal of Oilseed Brassica, 2026)
Seeds of Brassica juncea (L.) cultivar BIO 902 and Pusa Bold were treated with EMS (0.5%) and gammarays (900-1300 Gy) with the objective to study the variability for qualitative and quantitative traits, to isolatemorphological and economical mutants in M2 generation. Morphological mutants viz., early and late maturing,branched, appressed, tall and dwarf, powdery mildew tolerant and aphid tolerant and high yielding mutantswere identified. These mutants were isolated from all the treatments of gamma rays (900-1300 Gy) andcombination treatment of gamma rays and EMS (0.5%). These selected mutants will be forwarded to M3and further generations until homozygosity is reached and superior progenies will be evaluated in yield trials.